Responsibility on physical activity and health to adult over 40 years old in Tirana - ANDREA, Kristian; QELESHI, Anesti (Edelweiss Applied Science and Technology, 2025)
The health problem is more current than ever. There are positive relationships between physical activity and life satisfaction. All the above components are included in almost every training program, regardless of the age of the individual. The purpose of the study is to realize a clear and simple panorama on the engagement in physical activity among adults in the age group over 40 years old. The methodology will use the literature research method and observation method, utilizing CrossRef, PubMed, and Google Scholar. In conclusion, by physical activity, we mean systematic and regular exercise with the aim of achieving or maintaining high levels of the components of fitness. To achieve fitness, we must understand the difference between exercise and recreation. Moderate intensity physical activity is positively related to subjective well-being; however, the time spent on high intensity physical activity is negatively related to subjective well-being.